Neither myth nor stigma: Mainstreaming mental health in developing countries - Octavio Gómez-Dantés; Julio Frenk (Instituto Nacional de Salud Pública, 2018)
Mental and substance use disorders account for 18.9% of years lived with disability worldwide. A rising prevalence of mental disorders was identified in the past decade and a call for global attention to this challenge was made. The purpose of this paper is to discuss new strategies to address mental health problems in developing nations aimed at dealing with them within the frame of the overall health system. Mainstreaming mental disorders implies five dimensions of integration: i) incorporating mental health interventions to the global strategy to address non-communicable diseases; ii) moving away both from the biological and sociological reductionisms around mental health prevalent in the past century; iii) addressing the whole range of conditions related to mental health; iv) migrating from the idea that mental disorders have to be treated in secluded clinical spaces, and v) the use of a comprehensive approach in the treatment of these disorders.